1996
DOI: 10.1007/bf00114085
|View full text |Cite
|
Sign up to set email alerts
|

Cost efficiency of international insurance firms

Abstract: This article examines the cost efficiency of insurance firms located in 11 countries over a five-year period, 1988-1992. TwoX-inefficiency measures are derived, one from the stochastic cost frontier model and the other from the distribution-flee model. The results show that X-inefficiencies not only vary by country but by size and specialization. Firms in Finland and France have the lowest X-inefficiency, while firms in the United Kingdom have the highest. On average, small firms are more cost efficient than l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 21 publications
11
65
1
4
Order By: Relevance
“…4 viz. Cummins and Weiss (1993); Cummins et al (1996); Cummins and Zi (1998); Katrischen and Scordis (1998); Rai (1996). 5 For example in Diacon et al (2002); .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 viz. Cummins and Weiss (1993); Cummins et al (1996); Cummins and Zi (1998); Katrischen and Scordis (1998); Rai (1996). 5 For example in Diacon et al (2002); .…”
Section: Introductionmentioning
confidence: 99%
“…6 Fecher et al (1993); Gardner and Grace (1993); Fukuyama (1995); Cummins and Zi (1998). 7 Rai (1996); Cummins et al (1996); Donni and Fecher (1997); Katrischen and Scordis (1998); Diacon et al (2002). The paper is organized as follows: we describe the contextual setting, considering the Portuguese insurance sector in order to shed some light on the threats mentioned above; we survey the existing literature on the topic, with the aim of highlighting the contribution that the present paper seeks to make; we explain the theoretical framework supporting the model used; we present the data and results; we estimate the determinants of the efficient scores; we discuss the results; we put forward the limitations and possible extensions of the study; and finally, we make our concluding remarks.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that mergers and acquisitions, facilitated by the liberalized EU market, have led to efficiency gains. They also find similarly as Rai (1996) that larger firms and firms with high market shares operate at higher levels of cost inefficiency. Recently, Eling and Luhnen (2010) analysed efficiency with a comparison of 6462 insurers from 36 countries, and found that developed countries in Europe and Asia achieve higher efficiency scores than emerging markets.…”
Section: Introductionmentioning
confidence: 55%
“…Finally, they determine that cost inefficiency averages not less than 49%, and over the period studied there was an increase in both scale and allocative efficiency. Using a translog cost function, Bikker and Gorter (2011) Rai (1996) finds that, for the overall Dutch insurance industry in the period 1988-1992, the inefficiency estimate is 37% for large insurers and 28% for small firms. Eling and Luhnen (2010) use both SFA and DEA and study cost efficiencies in a 36 country sample over [2002][2003][2004][2005][2006].…”
Section: Literature Reviewmentioning
confidence: 99%